Analisa Penggunaan Koil Standart dan Koil Groundstrap Dengan Variasi Kawat dan Dimensi Lilitan Terhadap Unjuk Kerja Koil - Ahmad Zaenuri; Ikhwanul Qiram; Anas Mukhtar (Prodi Teknik Mesin Universitas PGRI Banyuwangi, 2018)
The study was conducted with a direct current DC motor ignition system circuit object with a 12 Volt battery source. This experiment compares a standard coil and a Groundstrap coil. The engine is varied with 2000 rpm, 5000 rpm and 8000 rpm. Engine speed is measured using a tachometer. Sparks are measured using the bar and the color of sparks is captured using a digital camera. Data retrieval is done with 3 replications. The data is averaged and a statistical test is performed. The results showed that the use of Groundstrap coil with wire variations and the dimensions of the coil affect the length of the spark jumps and the color of the sparks. There is a significant difference in the length of the spark jump between the standard coil and the Groundstrap coil. Standard coil lengths are longer out of focus than shorter focused Groundstrap coils and more blue sparks.